2023
DOI: 10.2174/1871520622666220901101204
|View full text |Cite
|
Sign up to set email alerts
|

The Impediments of Cancer Stem Cells and An Exploration into the Nanomedical Solutions for Glioblastoma

Abstract: Glioblastoma is an aggressive and reccurent tumour that affects our brain and spinal cord with an extensively poor prognosis and death of the patient within 14-15 months of diagnosis. The tumour originates from astrocytes and therefore comes under the glioma known as astrocytoma. These tumours exhibit miscellaneous properties and contain cancer stem cells (CSCs). The stem cells exhibit diverse mechanisms through which these cells indulge in the proliferation and renewal of their systems. CSCs pose a significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 149 publications
0
2
0
Order By: Relevance
“…Salinomycin has demonstrated a specific ability to target and eradicate CSCs, specifically in cases of breast cancer. Studies have shown that salinomycin is beneficial in decreasing the percentage of breast CSCs, which in turn hinders the growth and spread of tumors [ 79 ]. The specific focus on certain cells is one of the factors that has led to salinomycin being considered as a possible treatment for CSCs [ 78 ].…”
Section: Dual Role Of Autophagy In the Maintenance Of Cancer Stem Cellmentioning
confidence: 99%
“…Salinomycin has demonstrated a specific ability to target and eradicate CSCs, specifically in cases of breast cancer. Studies have shown that salinomycin is beneficial in decreasing the percentage of breast CSCs, which in turn hinders the growth and spread of tumors [ 79 ]. The specific focus on certain cells is one of the factors that has led to salinomycin being considered as a possible treatment for CSCs [ 78 ].…”
Section: Dual Role Of Autophagy In the Maintenance Of Cancer Stem Cellmentioning
confidence: 99%
“…Extensive research has shown that GSCs play an important role in glioblastoma and are associated with increased resistance to chemotherapy and radiotherapy, implying that GSCs have a significant impact on successful treatment outcomes and contribute significantly to the high recurrence rates seen in glioblastoma [ 4 , 5 , 6 ]. As a result, GSCs are considered prospective therapeutic targets for glioblastoma therapy, and eliminating GSCs is critical in treating glioblastoma [ 7 , 8 ]. GSC targeting is primarily focused on the direct ablation of GSC cell surface markers and certain pathways involved in GSC stemness maintenance.…”
Section: Introductionmentioning
confidence: 99%